2010
DOI: 10.1080/01490419.2010.518061
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Bay of Bengal Tropical Cyclones with WRF Model: Impact of Initial and Boundary Conditions

Abstract: An attempt is made to delineate the relative performances and credentials of GFS, FNL, and NCMRWF global analyses/forecast products as initial and boundary conditions (IBCs) to the WRF-ARW model in the simulation of four Bay of Bengal tropical cyclones (TCs). The results suggest that FNL could simulate horizontal advection of vorticity maxima at 850 hPa; hence, the tracks are more realistic with least errors as compared to GFS and NCMRWF. The mean landfall errors for 24-, 48-, and 72-hour forecasts are 73, 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 27 publications
(25 reference statements)
0
40
0
Order By: Relevance
“…In the second set of experiments known as the 3DVAR, the model IC is improved by insertion of satellite-derived wind observations using the 3DVAR analysis system. According to Mohanty et al (2010), the National Centers for Environmental Prediction (NCEP) FiNaL (FNL) analyses provided as IBCs to the mesoscale (WRF) model are better for prediction of TCs over Indian seas. Therefore, Downloaded by [Northeastern University] at 08:55 03 December 2014 in this study, for CNTL simulation, FNL analyses are used as IBCs for the model.…”
Section: Model Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second set of experiments known as the 3DVAR, the model IC is improved by insertion of satellite-derived wind observations using the 3DVAR analysis system. According to Mohanty et al (2010), the National Centers for Environmental Prediction (NCEP) FiNaL (FNL) analyses provided as IBCs to the mesoscale (WRF) model are better for prediction of TCs over Indian seas. Therefore, Downloaded by [Northeastern University] at 08:55 03 December 2014 in this study, for CNTL simulation, FNL analyses are used as IBCs for the model.…”
Section: Model Configurationmentioning
confidence: 99%
“…Hence, the global analyses which serve as initial and boundary conditions (IBCs) to mesoscale models (MMs) are ill-defined in representing the initial structure and position of the vortex. According to Mohanty et al (2010), the initial vortex position error in global analyses is about 100 km and further contributes to more track forecast errors. The primary and important task is to reduce the errors in initial conditions.…”
Section: Introductionmentioning
confidence: 98%
“…So the initial conditions may not be able to capture the intensity and location of the initial vortex to give correct forecast of TCs. Importance of accurate initial conditions is studied by Arpe et al (1985), Sanders (1987), Kuo and Reed (1988), Mohanty et al (2010). NWP being an initial value problem, Lorenz (1963) and Pielke (2006) have shown that even a small error in the initial condition (IC) may lead to a large error in the subsequent forecast.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that 30th April and 1st May initial conditions gives less landfall errors of 85 km and 50 km. Mohanty et al (2010) explored the impact of different sources of initial and boundary conditions on track and intensity of the Bay of Bengal cyclones.…”
Section: Introductionmentioning
confidence: 99%
“…Because of lack of sufficient conventional observations over the oceans where TCs form and evolve, the global analyses are ill-defined in representing the initial structure and position of the vortex. According to Mohanty et al (2010), the initial vortex position error in global analyses is about 80 -100 km and further contributes to more track forecast errors. The primary and important task is to reduce the errors in initial conditions.…”
Section: Introductionmentioning
confidence: 99%